Knee Arthritis in Children: When Can It Be Safely Treated With Needle Joint Aspiration? A Large Children's Tertiary Hospital Study. Issue 3 (March 2019) - Tornero, Eduard; De Bergua-Domingo, Josep Maria; Domenech, Pedro; Soldado, Francisco; Torner, Ferran; Castellanos, Juan; Soriano, Alex; Knörr, Jorge
Abstract : Background: Early joint decompression associated to antibiotic therapy is the most important procedure to reduce joint damage in septic knee arthritis in children. Several joint decompression methods have been described such as arthrotomy with open debriding, arthroscopic drainage or needle joint aspiration. The aim of the present study was to determinate which patients with acute septic knee arthritis could be safely treated with needle joint aspiration. Methods: Patients with an acute knee arthritis diagnosed between September 2003 and December 2013 in our children's tertiary hospital were retrospective review. All cases were initially treated with needle joint aspiration. Primary end-point was failure of joint aspiration. Results: A total of 74 patients were included in the study. Forty-two (56.8%) were male and median age was 1.49 years. Mean delay between onset of symptoms and diagnosis was 3.6 days and in 25 (33.8%) cases patients needed more than 1 visit to the emergency room. Median C-reactive protein (CRP) value was 36.3 mg/L and was >20 mg/L in 59 (79.7%) cases. A total of 11 (14.9%) patients showed failure of the joint aspiration treatment between 3 and 21 days after initial joint aspiration. The stepwise forward logistic regression model only identified as independent predictor of joint aspiration failure an age older than 3 years old (odds ratio, 5.64; 95% confidence interval, 1.38-29.61; P =0.018). Joint aspiration did not fail in any patient younger than 12 months and neither in any patient younger than 3 years old with CRP value <20 mg/L. Otherwise, treatment failed in 38% of patients older than 3 years and in 16% of patients between 1 and 3 years with a CRP>20 mg/L. Conclusions: Septic knee arthritis treated with needle joint aspiration succeed in all patients younger than 1 year and in all patients between 1 and 3 years with a CRP<20 mg/L. Alternative treatment such as arthroscopy debridement should be early considered in patients older than 3 years and patients between 1 and 3 years with CRP>20 mg/L. Level of Evidence: Level III.